Mechanisms of immunotherapy in cutaneous squamous cell carcinoma in the tumor microenvironment - Dong, Qinyi; Zhang, Zijian; Li, Siying; Liang, Lili (Frontiers in Immunology, 2025)
Cutaneous squamous cell carcinoma (cSCC) is a common cutaneous malignant tumor, with its development and progression closely linked to immune dysregulation within the tumor microenvironment (TME). This review highlights cSCC-specific TME features—such as UV-induced mutational burden and the immunosuppressive effects observed in transplant recipients—and systematically outlines the composition and functional roles of tumor cells, immune cells (Tregs, MDSCs, TAMs), and stromal cells (CAFs) within the TME. The immunosuppressive mechanisms mediated by these cellular components are clarified, particularly through pathways including PD-L1/PD-1 and TGF-β/Smad. Building on this foundation, the potential clinical value of immune checkpoint inhibitors (cemiplimab, pembrolizumab) in treating advanced cSCC is summarized based on data from relevant clinical trials. Additionally, the impact of gender differences on cSCC incidence and therapeutic outcomes is discussed. This review is distinguished from general tumor immunotherapy reviews by offering dedicated references for cSCC precision immunotherapy. In addition, priority is emphasized for future investigations into combination therapy regimens and the development of personalized tumor vaccines.